Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41433-022-01946-2
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness and its determinants in a geriatric population: a population-based study

Abstract: To determine the distribution of central corneal thickness (CCT) and its determinants in an Iranian geriatric population. METHODS: This population-based study was conducted in 2019 in Tehran, the capital of Iran, using stratified multistage random cluster sampling. The study population was all residents ≥60 years of age. First, preliminary optometric and ocular health examinations were performed including the measurement of uncorrected and best-corrected visual acuity, objective and subjective refraction, ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…We also demonstrated a negative correlation of CC and CCT, and similar results were also reported in previous studies with young subjects 12 , 26 . However, the correlation of CC and CCT may be positive in the elderly 27 , 28 . CC was also negatively correlated to CV-3 mm in the present study, but CC was not correlated to CV-5 mm, and was positively correlated to CV-7 mm, suggesting that the correlation of CC and CV may differ according to the area of interest.…”
Section: Discussionmentioning
confidence: 97%
“…We also demonstrated a negative correlation of CC and CCT, and similar results were also reported in previous studies with young subjects 12 , 26 . However, the correlation of CC and CCT may be positive in the elderly 27 , 28 . CC was also negatively correlated to CV-3 mm in the present study, but CC was not correlated to CV-5 mm, and was positively correlated to CV-7 mm, suggesting that the correlation of CC and CV may differ according to the area of interest.…”
Section: Discussionmentioning
confidence: 97%
“…16, No. 3, Mar.18, 2023 www.ijo.cn Tel: 8629-82245172 8629-82210956 Email: ijopress@163.com levels [13,33] , and CCT [10][11] affect IOP and they have different distribution among various communities. Considering the significant direct relationship between age and IOP observed in the present study, it seems that the older age range of study participants is the main reason for the higher mean IOP compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an increase [4][5] , some decrease [6][7] , and some no change [8][9] in IOP with advancing age. Since age influences many parameters affecting IOP, including corneal thickness [10][11] , blood pressure (BP) [12][13] , pulse [13][14] , and body mass index (BMI) [13][14][15] , the role of these parameters should be considered in the interpretation of the results. Sociodemographic and non-ocular factors are said to be responsible for 10% of IOP variations.…”
Section: Introductionmentioning
confidence: 99%